2020
DOI: 10.1136/bmjebm-2020-111407
|View full text |Cite
|
Sign up to set email alerts
|

Blinding in randomised clinical trials of psychological interventions: a retrospective study of published trial reports

Abstract: ObjectivesTo study the extent of blinding in randomised clinical trials of psychological interventions and the interpretative considerations if randomised clinical trials are not blinded.DesignRetrospective study of trial reports published in six high impact factor journals within the field of psychiatry in 2017 and 2018.SettingTrial reports published in World Psychiatry, JAMA Psychiatry, Lancet Psychiatry, American Journal of Psychiatry, British Journal of Psychiatry, or Psychotherapy and Psychosomatics.Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 109 publications
2
56
0
2
Order By: Relevance
“…A systematic review on methods of masking in randomized controlled trials with pharmacologic treatments concluded that reporting of condition masking is generally 'quite poor', and based on trials that have tested the success of masked methods, a high proportion of studies are effectively unmasked (Boutron et al 2006). This corroborates a recent systematic review of studies published in top psychiatry journals in 2017 and 2018, which found that only 59% of the trial reports included adequate reporting of masking outcomes (Juul et al 2020). Similarly, a comprehensive literature search found that masking was not maintained in 20/23 "double-blind" studies examining psychotropic drugs (Fisher and Greenberg 1993).…”
Section: Modern Era Clinical Research Design Elementssupporting
confidence: 84%
“…A systematic review on methods of masking in randomized controlled trials with pharmacologic treatments concluded that reporting of condition masking is generally 'quite poor', and based on trials that have tested the success of masked methods, a high proportion of studies are effectively unmasked (Boutron et al 2006). This corroborates a recent systematic review of studies published in top psychiatry journals in 2017 and 2018, which found that only 59% of the trial reports included adequate reporting of masking outcomes (Juul et al 2020). Similarly, a comprehensive literature search found that masking was not maintained in 20/23 "double-blind" studies examining psychotropic drugs (Fisher and Greenberg 1993).…”
Section: Modern Era Clinical Research Design Elementssupporting
confidence: 84%
“…Fourth, even though the study is among the larger naturalistic studies focusing exclusively on AvPD, the number of included participants was still small, so there is an urgent need for replication in larger samples. Fifth, nearly all measures were based on self-reporting, which is subject to biases (Juul et al, 2021). Sixth, although we chose to report remission rates, these results should be interpreted with caution owing to the methodological problems associated with dichotomization of continuous scales (Altman and Royston, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, we will carefully consider the low sample size when interpreting the trial results. Fourth, as participants are not blinded to the allocated treatment, results from all participant-reported outcomes are at risk of bias [ 10 ]. Fifth, therapists are likewise not blinded to the allocated treatment and may have an allegiance to one of the interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome assessors, data managers, statisticians, the data safety and monitoring committee, and decision-makers will be blinded to treatment allocation [ 10 ]. Trial participants and therapists will not be blind to the treatment allocation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation